ANALISIS PERLINDUNGAN HUKUM TERHADAP HEWAN LIAR YANG TERANIAYA DAN DIPERJUALBELIKAN (STUDI KASUS: PERDAGANGAN DAGING KUCING DAN ANJING DI PASAR TOMOHON SULAWESI UTARA) - Yunita Wahyu Medyawati; Mella Ismelina Farma Rahayu (Jurnal Hukum Adigama, 2021)
The city of Tomohon is famous for its extreme market that sells various animal meats that are not commonly consumed in some areas. The official name of the market is Tomohon City Faith Market. A number of animals whose meat is sold in this market include cats, dogs, bats, forest rats, wild boars, cattle pigs, snakes, etc. In this case, it is quite interesting to note that cats and dogs are not livestock that can be consumed, but wild animals and/or pets that should be human friends. The main problem in this study is the slaughtering method carried out by a number of Tomohon Market traders against cats and dogs which are considered very inhumane and against religious rules and laws. This study aims to determine the form of legal protection for wild animals that are abused and traded in the Tomohon Market, North Sulawesi. This research uses a descriptive empirical juridical method. The data sources used are primary, secondary, and tertiary data. The results of this study indicate that traders do not treat cats and dogs as they should in the Law and Animal Welfare, and many residents of North Sulawesi still consume these animals. It can be concluded that the trade in cat and dog meat is not only bad for animals, it is also bad for human health.